Peran Guru Dalam Mengoptimalkan Kecerdasan Kinestetik Melalui Senam Aku Cinta Indonesia Di TK Dharma Wanita Desa Lilibooi - Vinny Alvionita Hetharion; Dewi Tika Lestari; Wilhelmus Labobar (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2025)
Abstract: This study aims to analyze and describe the role of teachers in optimizing children's kinesthetic intelligence through the Aku Cinta Indonesia (ACI) gymnastics activity at TK Dharma Wanita Lilibooi Village. Kinesthetic intelligence refers to an individual's ability to use the body effectively to express ideas, emotions, and motor skills through coordination, balance, agility, and movement control. In early childhood education, the development of this intelligence is very important because it is closely related to children's physical, cognitive, and social development. This research employed a descriptive qualitative approach using a field study method. Data were collected through observation, interviews, and documentation involving teachers, the school principal, and children’s activities during the gymnastics sessions. The findings indicate that teachers play a significant role as facilitators, motivators, role models, and evaluators in the implementation of ACI gymnastics. Teachers design simple movements, demonstrate them directly, use engaging music, and provide motivation and guidance to encourage children to move actively and confidently. Support from the school principal through the provision of facilities, training, and supervision also strengthens the success of the activity. Supporting factors include children’s enthusiasm, teacher creativity, and adequate school facilities, while inhibiting factors include differences in children’s motor abilities, shyness, and physical conditions. Therefore, the Aku Cinta Indonesia gymnastics activity is proven to be effective in stimulating the development of children’s kinesthetic intelligence in a fun and gradual manner. Keywords: The Role of Teachers, Kinesthetic Intelligence; Aku Cinta Indonesia Gymnastics